Using the active listening method in forming the communicative competence of economics students during professional Ukrainian classes - Кириченко, Ю. (Teaching Languages at Higher Educational Establishments at the Present Stage. Intersubject Relations, 2017)
An important aim of the Ukrainian language (for professional purposes) course for higher economic education institutions is to develop communicative competence. Students of economic specialties are offered uniform kinds of communicative activity inherent in their profession. A leading economist training area is communication strategies in business. The problem of interpersonal communication in business is at the intersection of economic, psychological, philosophical and linguistic research studies. Over the last decade, scientists have demonstrated a marked increase in their interest in this problem. The author proposes that the results of this study can be used to efficiently implement the guidelines of the Ministry of Education and Science of Ukraine about communicative skills during the Ukrainian language classes. There have been offered various activities that would help students to form complex language skills and knowledge they need during their studies and further professional engagement.One of the important factors that affect the performance of these types of business communication is the ability to tailor well-aimed speech instruments for conflict resolution. The author recommends applying one of the most common methods used by modern psychologists in business communication, which is reflexive (emphatically, active) listening, during the Ukrainian language classes for professional purposes At the heart of these psychological and marketing techniques, there is a linguistic component. They could be applied during Ukrainian classes, as they involve the use of certain speech patterns that can be productive for the development of successful professional communication skills. The ability to speak accurately and correctly during business communication is one of the important keys to professional success, so mastering these skills is important in the language training of students of economic specialties. The defined methods could be also used for conflict resolution, which is also considered an important communicative skill.